Long-term Serologic Follow-up of Children Vaccinated with a Pediatric Formulation of Virosomal Hepatitis A Vaccine Administered With Routine Childhood Vaccines at 12–15 Months of Age. Issue 7 (July 2016) - Dagan, Ron; Ashkenazi, Shai; Livni, Gilat; Go, Oscar; Bagchi, Partha; Sarnecki, Michal
Abstract : Background: : The aim of this open-label, active-controlled, parallel group, phase 2 follow-up study was to assess the long-term immunogenicity of Epaxal Junior, the pediatric dose of an aluminum-free virosomal inactivated hepatitis A virus (HAV) vaccine, in children receiving routine childhood vaccines (RCV). Methods: Healthy children (12–15 months old, ≥8 kg weight) were randomized (1:1:1) to group A: Epaxal Junior + RCV (day 1); group B: Epaxal Junior (day 1) + RCV (day 29) and group C: Havrix 720 + RCV (day 1). All 3 groups received 2 doses of HAV vaccines 6 months apart. Children who completed the primary study were followed up from 18 months to 7.5 years post booster. Results: Of 291/327 randomized children who had completed the primary study, 157 were followed for the 7.5-year analysis (group A: 50; group B: 54; and group C: 53). Of these, 152 children had protective levels of anti-HAV antibodies [≥10 mIU/mL; 98% (group A); 96.3% (group B); 96.2% (group C)]. Anti-HAV geometric mean concentrations were similar in groups A and B at all the time points (1.5-, 2.5-, 3.5-, 5.25- and 7.5-year time point) but slightly lower in group C. Predictions of the median duration of persistence of seroprotective antibody levels, using the linear mixed model were similar in all groups: (group A: 19.1 years, group B: 18.7 years, group C: 17.3 years). Conclusions: Immunization with Epaxal Junior administered with RCVs at 12 months elicited protective response beyond 7.5 years in almost all children. Assessing the kinetic of anti-HAV antibody titers decline over time, the moment to reach antibody concentrations below the accepted protective level may occur earlier than previously estimated.